Rapid Adaptation to Temperature via a Potential Genomic Island of Divergence in the Invasive Green Crab, Carcinus maenas - Tepolt, Carolyn K.; Palumbi, Stephen R. (Frontiers in Ecology and Evolution, 2020)
Widespread species often adapt easily to novel conditions – both those found in new habitats and those generated by climate change. However, rapid adaptation may be hindered in the marine realm, where long-distance dispersal and consequently high gene flow are predicted to limit potential for local adaptation. Here, we use a highly dispersive invasive marine crab to test the nature and speed of adaptation to temperature in the sea. Using single nucleotide polymorphisms (SNPs) generated from cardiac transcriptome sequencing, we characterized six populations of the European green crab (Carcinus maenas) located across parallel thermal gradients in their native and invasive ranges. We compared SNP frequencies with local temperatures and previously-generated data on cardiac heat and cold tolerance to identify candidate markers associated with population-level differences in thermal physiology. Of 10,790 SNPs, 104 were identified as frequency outliers, a signal that was strongly driven by association with temperature and/or cold tolerance. Seventy-two of these outlier markers, representing 28 different genes, were in a cluster of SNPs identified as a potential inversion polymorphism using linkage disequilibrium network analysis. This SNP cluster was unique in the data set, which was otherwise characterized by low levels of linkage disequilibrium, and markers in this cluster showed a significant enrichment of coding substitutions relative to the full SNP set. These 72 outlier SNPs appear to be transmitted as a unit, and represent a putative genomic island of divergence which varied in frequency with organismal cold tolerance. This relationship was strikingly similar across both native and invasive populations, all of which showed a very strong correlation with cold tolerance (R2 = 0.96 over all six populations). Notably, three of these populations have diverged recently (<100 years) and show little to no neutral divergence, suggesting that this genomic region may be responding to temperature on a relatively short time scale. This relationship indicates adaptation to temperature based on the action of a putative genomic island of divergence, perhaps partially explaining the extraordinary invasive ability of this species.